Complete Genome Sequence of Vibrio campbellii LMB 29 Isolated from Red Drum with Four Native Megaplasmids - Liu, Jinxin; Zhao, Zhe; Deng, Yiqing; Shi, Yan; Liu, Yupeng; Wu, Chao; Luo, Peng; Hu, Chaoqun (Frontiers in Microbiology, 2017)
Vibrio spp. are the most common pathogens for animals reared in aquaculture. Vibrio campbellii, which is often involved in shrimp, fish and mollusks diseases, is widely distributed in the marine environment worldwide, but our knowledge about its pathogenesis and antimicrobial resistance is very limited. The existence of this knowledge gap is at least partially because that V. campbellii was originally classified as Vibrio harveyi, and the detailed information of its comparative genome analysis to other Vibrio spp. is currently lacking. In this study, the complete genome of a V. campbellii predominant strain, LMB29, was determined by Miseq in conjunction with PacBio SMRT sequencing. This genome consists of two circular DNA chromosomes and four megaplasmids. Comparative genome analysis indicates that LMB29 shares a 96.66% similarity (average nucleotide identity) with the V. campbellii ATCC strain BAA-1116 based on a 75% AF (average fraction) calculations, and its functional profile is very similar to V. campbellii E1 and V. campbellii CAIM115. Both T3SS and T6SS, along with the tlh gene which encodes a thermolabile hemolysin, are present in LMB29 which may contribute to the bacterial pathogenesis. The virulence of this strain was experimental confirmed by performing a LDH assay on a fish cell infection model, and cell death was observed as early as within three hours post infection. Thirty-seven antimicrobial resistance genes (>45% identity) were predicted in LMB29 which includes a novel rifampicin ADP ribosyltransferase, arr-9, in plasmid pLMB157. The gene arr-9 was predicted on a genomic island with horizontal transferable potentials which may facilitate the rifampicin resistance dissemination. Future researches are needed to explore the pathogenesis of V. campbellii LMB29, but the availability of this genome sequence will certainly aid as a basis for further analysis.